Hungarian Algorithm using Haar Tuples to Solve Fuzzy Travelling Salesman Problem - Dhanasekar, S.; Kumar Dash, Saroj; Hariharan, S. (International Journal of Engineering and Technology, 2018)
Travelling salesman problem(TSP) deals with visiting all the given cities and return back to the starting city with the minimum travelling distance or minimum travelling cost where each city is visited exactly once. The TSP problem is a special kind of an assignment model that excludes sub tours.  In this paper we used Haar Hungarian algorithm approach [13] to solve a Fuzzy Travelling Salesman Problem (FTSP) and Numerical examples are given to validate the proposed algorithm.